Boom or bust, extractives are no longer saviours: The need for robust tax regimes in Gulf countries - Alexander Ezenagu (17052399) (2021)
Over the last decades, extractive industries, especially the oil and gas sectors, have generated significant economic activity and growth in countries in the Gulf Cooperation Council (GCC). However, recent drop in oil prices and other extractive products signal a bust cycle for many of these GCC countries. In addition, the global transition to low carbon energy sources could mean that the economic mainstays of GCC countries could be threatened. With vast extractives revenue, GCC countries have over the years granted huge tax incentives to investors, have few tax bases, and a not so deep tax net. While a country has the power to exercise its fiscal sovereignty as it deems fit, studies show that effective tax systems could mobilize needed revenue for development, achieve redistributive justice and enhance sustainable development. This article examines the need for efficient, transparent and accountable tax systems in Gulf countries as a way of sustaining economic growth and wealth creation in light of dwindling extractive revenue. The article takes into account the cultural impact and regressive nature of taxes in the GCC countries and discusses ways to address the externalities which will arise from the adoption of robust tax systems. It also recommends that GCC countries broaden their tax bases to achieve diversification of revenue resources and encourage representation. Other Information Published in: The Extractive Industries and Society License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.exis.2020.11.014